Response of photosynthetic characteristics and yield of grape to different CO2 concentrations in a greenhouse - Zhou, Yufan; Mahmoud Ali, Hossam Salah; Xi, Jinshan; Yao, Dongdong; Zhang, Huanhuan; Li, Xujiao; Yu, Kun; Zhao, Fengyun (Frontiers in Plant Science, 2024)
Due to the enclosed environment of greenhouse grape production, the supply of CO2 required for photosynthesis is often insufficient, leading to photosynthetic down regulation and reduced yield. Currently, the optimal CO2 concentration for grape production in greenhouses is unknown, and precise control of actual CO2 levels remains a challenge. This study aims to investigate the effects of different CO2 concentrations on the photosynthetic characteristics and yield of grapes, to validate the feasibility of a CO2 gas irrigation system, and to identify the optimal CO2 concentration for greenhouse grape production. In this study, a CO2 gas irrigation system combining CO2 enrichment and gas irrigation techniques was used with 5-year-old Eurasian grape variety (Vitis Vinifera L.) 'Flame Seedless'. Four CO2 concentration treatments were applied: 500 ppm (500 ± 30 µmol•mol -1 ), 700 ppm (700 ± 30 µmol•mol -1 ), 850 ppm (850 ± 30 µmol•mol -1 ), and 1000 ppm (1000 ± 30 µmol•mol -1 ).As CO2 concentration increased, chlorophyll a, chlorophyll b and carotenoids in grape leaves all reached maximum values at 700 ppm and 850 ppm during the same irrigation cycle, while the chlorophyll a/b ratio was lower than at other concentrations. The net photosynthetic rate (Pn) and water use efficiency (WUE) of grape leaves were highest at 700 ppm. The transpiration rate and stomatal conductance at 700 ppm and 850 ppm were significantly lower than those at other concentrations. The light saturation point and apparent quantum efficiency reached their maximum at 850 ppm, followed by 700 ppm.Additionally, the maximum net photosynthetic rate, carboxylation efficiency, electron transport rate, and activities of SOD, CAT, POD, PPO, and Rubisco at 700 ppm were significantly higher than at other concentrations, with the highest yield recorded at 14.54 t•hm -2 . However, when the CO2 concentration reached 1000 ppm, both photosynthesis and yield declined to varying degrees. Under the experimental conditions, the optimal CO2 concentration for greenhouse grape production was 700 ppm, with excessive CO2 levels gradually inhibiting photosynthesis and yield. The results provide a theoretical basis for the future application of CO2 fertilization and gas irrigation techniques in controlled greenhouse grape production.